2017
DOI: 10.1364/boe.8.001771
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal nonlinear optical microscopy reveals critical role of kinesin-1 in cartilage development

Abstract: Abstract:We developed a multimodal nonlinear optical (NLO) microscope system by integrating stimulated Raman scattering (SRS), second harmonic generation (SHG) and twophoton excited fluorescence (TPEF) imaging. The system was used to study the morphological and biochemical characteristics of tibial cartilage in a kinesin-1 (Kif5b) knockout mouse model. The detailed structure of fibrillar collagen in the extracellular matrix of cartilage was visualized by the forward and backward SHG signals, while high resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…This phenomenon was reported as an intracellular collagen fibril formation in a study of Kif5b-depleted mutant mice cartilage. 29 However, to the best of our knowledge, this type of collagen formation has not been reported in normal chondrocytes of articular cartilage. It is unknown whether this is a pathological or a normal physiological process.…”
Section: Discussionmentioning
confidence: 80%
“…This phenomenon was reported as an intracellular collagen fibril formation in a study of Kif5b-depleted mutant mice cartilage. 29 However, to the best of our knowledge, this type of collagen formation has not been reported in normal chondrocytes of articular cartilage. It is unknown whether this is a pathological or a normal physiological process.…”
Section: Discussionmentioning
confidence: 80%
“…KIF5B may have some cytokinesis independent roles in the chondrocytes. We have reported that the secretion of extracellular matrix proteins was affected in the mutant [14]. We also observed that the disruption of terminal differentiation of the chondrocytes and cell death in the mutant growth plate, which may not be directly related to the cytokinetic defect.…”
Section: Discussionmentioning
confidence: 88%
“…Vesicular trafficking defects have been implicated in low bone mass phenotypes and bone fragility that are at least partly attributed to failure in collagen secretion [48][49][50]. Interestingly, impaired secretion of type II collagen has been demonstrated in Kif5b-deficient chondrocytes [14,51]. In proband 1 fibroblasts, type I collagen electrophoresis did not suggest a qualitative or quantitative collagen defect (S1 Fig) . More research is needed to determine whether impaired collagen secretion is contributing to the phenotype in KIF5B-related osteogenesis imperfecta.…”
Section: (Fig 1d)mentioning
confidence: 99%